Type I and type II Helicobacter pylori infection status and their impact on gastrin and pepsinogen level in a gastric cancer prevalent area - Yuan, Lin (World J Gastroenterol, 2020)
BACKGROUND: Type I Helicobacter pylori (H. pylori) infection causes severe gastric inflammation and is a predisposing factor for gastric carcinogenesis. However, its infection status in stepwise gastric disease progression in this gastric cancer prevalent area has not been evaluated; it is also not known its impact on commonly used epidemiological gastric cancer risk markers such as gastrin-17 (G-17) and pepsinogens (PGs) during clinical practice. AIM: To explore the prevalence of type I and type II H. pylori infection status and their impact on G-17 and PG levels in clinical practice. METHODS: Thirty-five hundred and seventy-two hospital admitted patients with upper gastrointestinal symptoms were examined, and 523 patients were enrolled in this study. H. pylori infection was confirmed by both (13)C-urea breath test and serological assay. Patients were divided into non-atrophic gastritis (NAG), non-atrophic gastritis with erosion (NAGE), chronic atrophic gastritis (CAG), peptic ulcers (PU) and gastric cancer (GC) groups. Their serological G-17, PG I and PG II values and PG I/PG II ratio were also measured. RESULTS: A total H. pylori infection rate of 3572 examined patients was 75.9%, the infection rate of 523 enrolled patients was 76.9%, among which type I H. pylori infection accounted for 72.4% (291/402) and type II was 27.6%; 88.4% of GC patients were H. pylori positive, and 84.2% of them were type I infection, only 11.6% of GC patients were H. pylori negative. Infection rates of type I H. pylori in NAG, NAGE, CAG, PU and GC groups were 67.9%, 62.7%, 79.7%, 77.6% and 84.2%, respectively. H. pylori infection resulted in significantly higher G-17 and PG II values and decreased PG I/PG II ratio. Both types of H. pylori induced higher G-17 level, but type I strain infection resulted in an increased PG II level and decreased PG I/PG II ratio in NAG, NAGE and CAG groups over uninfected controls. Overall PG I levels showed no difference among all disease groups and in the presence or absence of H. pylori; in stratified analysis, its level was increased in GC and PU patients in H. pylori and type I H. pylori-positive groups. CONCLUSION: Type I H. pylori infection is the major form of infection in this geographic region, and a very low percentage (11.6%) of GC patients are not infected by H. pylori. Both types of H. pylori induce an increase in G-17 level, while type I H. pylori is the major strain that affects PG I and PG IIs level and PG I/PG II ratio in stepwise chronic gastric disease. The data provide insights into H. pylori infection status and indicate the necessity and urgency for bacteria eradication and disease prevention in clinical practice.